ОБЩИЕ ПОНЯТИЯ О ГРУНТОВЫХ И БЕТОННЫХ ПЛОТИНАХ - Сабитова , Ирода Иброхим қизи; Асмандиярова, Регина Бахтиер қизи; Sabitova, Iroda Ibrokhim qizi; Asmandiyarova, Regina Baxtiyor qizi (Educational Research in Universal Sciences, 2023)
This article discusses the general concepts of soil and concrete dams, their types, calculations and advantages.